TINGKAT KECEMASAN ATLET MENGHADAPI PERTANDINGAN PADA ATLET SEPAK BOLA USIA 21 TAHUN PUTRA WIJAYA FC - Apriyanti Rahmalia; Meiriani Armen; Faridatul Ala (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
Abstract ____________________________________________________________ This study aims to determine the level of anxiety of 21-year-old soccer athlete Putra Wijaya FC when facing a match. The anxiety level faktor in question is the Intrinsic and Extrinsic faktor. This research is a descriptive research.. The sample in this study were all 21-year-old soccer athletes, Putra Wijaya FC, totaling 25 people. The instrument used in this study was a questionnaire compiled using a Likert scale. The data were analyzed descriptively with the percentage formula then categorized into five categories based on the mean value and ideal standard deviation. The results showed, on the intrinsic anxiety faktor that the highest frequency was in the High category with a total of 11. The percentage of the highest frequency was 44%. The lowest frequency is in the Low and Very Low categories with a total of 3 and a percentage of 12%. In the extrinsic anxiety faktor, the highest frequency is in the High Category with a total of 10 people. The highest frequency percentage is 40%. The lowest frequency is in the Very Low category with a total of 2 and a percentage of 8%.